Multi-time scale analysis of the water level minima in Lake Titicaca over the past 103 years - Sulca, Juan; Vuille, Mathias; Takahashi, Ken; Roundy, Paul; Dong, Bo; Mayta, Victor; Tacza, Jose; Apaestegui, James (Frontiers in Climate, 2025)
Lowest events in Lake Titicaca’s water level (LTWL) significantly impact local ecosystems and the drinking water supply in Peru and Bolivia. However, the hydroclimatic mechanisms driving extreme lake-level lowstands remain poorly understood. To investigate these low lake-level events, we analyzed detrended monthly LTWL anomalies, sea surface temperature (SST) datasets covering the period 1921–2023. ERA5 reanalysis covers the period 1940–2023. A multiple linear regression model was developed to compute detrended LTWL anomalies, excluding multidecadal and residual components. Interdecadal Pacific Oscillation (IPO) and Pacific Decadal Oscillation (PDO) indices were also analyzed for the same period. Results indicate that 25% of all LTWL minima events have a short duration of <5 months, while the remaining 75% of all events have a long duration of more than 9 months, respectively. All long-lived LTWL minima events are associated with reduced moisture flow from the Amazon basin toward Lake Titicaca, but the large-scale forcing varies with the phase change of the decadal component in the 11–15 years band of the PDO (PDO11–15 years). Under warm PDO11–15 years phases, LTWL minima are driven by an enhanced South American low-level jet (SALLJ) caused by warm SST anomalies over the eastern Pacific Ocean. Warm SST anomalies over tropical North Atlantic and central Pacific cold events, which reinforce the cold PDO11–15 years phases, driving long-lived LTWL minima through the reduction of SALLJ. Conversely, long-lived LTWL minima events under neutral PDO11–15 years phases are caused by westerly flow anomalies confined to the Peruvian Altiplano. Therefore, PDO and IPO do not drive long-lived LTWL minima events because their relationship does not remain consistent over time. In conclusion, long-lived LTWL minima events exhibit a regional nature and are not driven by the PDO or IPO, as LTWL shows no consistent relationship with these decadal SST modes over time.